Electrochemical sensing of biomarker for diagnostics of bacteria-specific infections. (August 2016) - Alatraktchi, Fatima AlZahra'a; Johansen, Helle Krogh; Molin, Søren; Svendsen, Winnie Edith
Aim: Pseudomonas aeruginosa is a pathogen that is prevalent in serious infections in compromised patients worldwide. A unique virulence factor of this bacterium is the redox-active molecule pyocyanin, which is a potential biomarker for the identification of P. aeruginosa infections. Here we report a direct, selective and rapid detection technique of pyocyanin.Materials & methods: Pyocyanin was detected by amperometry at a relatively high potential where the pyocyanin signal was unaffected by background contributions.Results & conclusion: Pyocyanin was detected at concentrations down to 125 nM in a 50 µM mixture of interfering compounds with a reproducibility of r 2 = 0.999 (n = 5) within 200 s. The results document a step toward a point-of-care technique for diagnosis of P. aeruginosa infections.